FINTECH SEBAGAI FAKTOR MODERASI LOCAL BRAND UNTUK MENINGKATKAN KEUNGGULAN BERSAING UMKM - Restia Christianty; Walter Tabelessy (Media Bina Ilmiah, 2025)
This study aims to examine the role of local brands in strengthening the competitive advantage of micro, small, and medium enterprises (MSMEs), with financial technology (fintech) employed as a moderating variable. The research is motivated by the growing consumer preference for authentic local products rooted in cultural values, along with the increasing adoption of fintech as an enabler for transaction efficiency and financial management. The investigation was conducted on Djikoe Ngopi, an MSME located in Ambon city, using a quantitative survey approach. Respondents were selected through purposive sampling, considering their experience in utilizing fintech services. Data were analyzed with Structural Equation Modeling based on Partial Least Squares (PLS-SEM) using Adanco software. The findings reveal that local brands significantly enhance competitive advantage by creating differentiation and building consumer loyalty. Fintech also exerts a direct and significant influence on competitive advantage through its role in providing efficient and secure financial services. Moreover, fintech strengthens the impact of local branding by aligning cultural authenticity with digital convenience, thereby generating sustainable competitive advantage. The study contributes theoretically by extending the Resource Based View (RBV) into the digital context, while practically offering insights for MSMEs to combine cultural differentiation with fintech adoption to remain competitive in the digital economy era..